Erdheim-Chester Disease in a Female Cardiac Surgery Patient - Mahoozi, H. R.; Zittermann, A.; Hakim Meibodi, K.; Burchert, W.; Gummert, J. F.; Mirow, N. (The Thoracic and Cardiovascular Surgeon, 2012)
We report a case of Erdheim-Chester disease (ECD) with isolated cardiac involvement in a 74-year-old female patient. The patient initially presented with superior vena cava syndrome and PET-CT imaging demonstrating an obstructing hypermetabolic lesion in the right atrium, and a distinct nonobstructing hypermetabolic lesion in the left atrium, expected to be malignant. There was no evidence of extracardiac disease. At surgical exploration, consistent with malignancy, the right atrial tumor was found to have grown into the pericardium and was resected to address symptoms and for histological diagnosis which revealed ECD on immunohistochemistry. We conclude that isolated cardiac ECD should be included in the surgical strategy for cardiac tumors showing infiltrative growth.
Keywords: cardiac; inflammation; systemic (incl. cells, mediators); tumor; Erdheim-Chester disease; non-Langerhans cell histiocytosis; immunohistochemical staining; cardiac tumor